South Africa’s Economic Foreign Policy: A Study of Slow Maturation - Nemalili, Lusani (University of the Witwatersrand, Johannesburg, 2023)
In the international environment, all state relations are guided by a foreign policy that conveys what a state intends to achieve through its relations with other states. Foreign policy is the means used to express a state’s national interests internationally to other states whilst executing on its domestic policy making, strategies and decisions. Therefore, foreign policy is the translation of domestic national interests to an international audience for engagement. However, national interests vary according to what the state aims to fulfil abroad. They could be economic, social, security, political interests. Nevertheless, it remains critical that economic interests have always dominated the international relations arena. Thus, a convergence of foreign policy and domestic economic policy of a state are crucial for its international success that contributes to its economic growth within and beyond its borders. This convergence produces an economic foreign policy. An economic foreign policy then guides the decisions of policymakers and diplomatic practices of the state bureaucracy in achieving the state’s national interests abroad. The presence of an economic foreign policy in a state is important because decisions that different actors (state and non-state) make in the international environment have to be accounted for and guided by a policy in order to understand the reasoning and logic behind them. The absence of an economic foreign policy enables a state to operate on an ad hoc decision-making basis in the international environment and with outcomes whose impact cannot be measured nor monitored by the state itself or other states intending to form economic relations with it. South Africa, with its economic interests, goals and a foreign policy, has not yet produced a coherent, codified and well-expressed economic foreign policy for an international audience. Whilst the country has relevant actors and the right processes to produce an economic foreign policy, it has not brought one into maturity through the consolidation and unification of foreign and economic policies of the state. This is due to several domestic conditions in policy making, decisions and processes that prohibit the realisation of an economic foreign policy. It is in these domestic foreign and economic policy making environments that the enquiry of this study is found to reveal the reasons why South Africa has not had a matured economic foreign policy since the new democratic dispensation of 1994.
Dissertation submitted in full requirements for a Master of Arts Degree International Relations Department, School of Social Sciences, Faculty of Humanities, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Economic foreign policy; Slow maturation; Economic policy; Department of International Relations and Cooperation; Department of Trade, Industry and Competition; Foreign policy; Economic foreign policy making; Decisions; Fluidity; Politicization; Ideology; Exclusion; Proliferation of actors; UCTD; SDG-8: Decent work and economic growth